Business Sustainability & Economic Consequences : A Case of A Developing Country - Malaysia - Hamdi, Aishath Asna (2015)
The key to assessing the economic consequences of business sustainability depends on the way business sustainability is measured and this is greatly influenced by the level of information disclosure on business sustainability initiatives by the firms. Subsequently, these levels of disclosures are highly affected by the way firms define and interpret business sustainability. In this context this paper aims highlights about the conceptual issues in literature while conceptualising the notion of business sustainability, also seek to find answers in contemporary methods to quantify business sustainability. In this regard, this paper will highlight upon the ways literature has described business sustainability and to understand the challenges faced by both academics and firms in defining this concept. Since economic consequences can be defined in multitudinous ways, to avoid further confusions, within the context of this paper economic consequences are viewed in terms of financial benefits. Therefore, special consideration should be given while conceptualising the economic consequences, as it does not include any social and sustainability development benefits. Secondly, this paper will also reflect upon the multiple ways firms disclose business sustainability initiatives, and also highlight the critical challenges faced by both academics and firms in quantifying business sustainability. In this regard, this paper will also gives an insight on how firms derive value through business sustainability and whether is there any merits to the business case of business sustainability. It is also noted that, most of the literature and empirical evidences to measure business sustainability and their economic consequences are mostly,based on developed countries and little is known about the effects of implementation of business sustainability in the context of developing countries. In this context, this paper is based on the study conducted to investigate the economic consequences of business sustainability in Malaysia a booming developing country. Therefore, the issues highlighted in this paper is a reflection of the findings gathered from that study (group project) and as a basis to better understand the conceptual issues in quantifying the economic consequences of business sustainability in a developing country’s perspective.